2010
DOI: 10.1038/nn.2624
|View full text |Cite
|
Sign up to set email alerts
|

Plk2 attachment to NSF induces homeostatic removal of GluA2 during chronic overexcitation

Abstract: Trafficking of AMPA receptors is important for many forms of synaptic plasticity. However, the link between activity and resulting synaptic alterations is not fully understood. Here, we identified a direct interaction between NSF, an ATPase involved in membrane fusion events and stabilization of surface AMPARs, and Plk2, an activity-inducible kinase that homeostatically decreases excitatory synapse number and strength. Plk2 disrupted interaction of NSF with the GluA2 subunit of AMPARs, promoting extensive loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 51 publications
(91 reference statements)
3
65
0
Order By: Relevance
“…A previous study has reported that, in COS-7 cells, chronic overexcitation impaired homeostatic synaptic plasticity by decreasing AMPA receptor expression (66). Indeed, decreased expression of tyrosine hydroxylase and dopamine ␤ hydroxylase is known to occur in LC neurons of Mecp2-null mice, leading to insufficient NE biosynthesis (5,67).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that, in COS-7 cells, chronic overexcitation impaired homeostatic synaptic plasticity by decreasing AMPA receptor expression (66). Indeed, decreased expression of tyrosine hydroxylase and dopamine ␤ hydroxylase is known to occur in LC neurons of Mecp2-null mice, leading to insufficient NE biosynthesis (5,67).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies in which manipulations of proteins that interact with the AMPAR endocytic machinery were shown to perturb the steady-state number of AMPAR at synaptic sites (26). CPG2 function may have particular significance in the context of synaptic plasticity, because regulated AMPAR internalization plays a critical role in several forms of synaptic plasticity, including LTD (27,28) and homeostatic synaptic down-scaling (29).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, Plk2 controls multiple pathways beyond small GTPases, 41 and understanding the interplay of these pathways with each other and with other known homeostatic proteins such as Arc will be of importance Figure 2. Microdomains of ras/rap signaling mediated by GaPs/GEFs.…”
Section: Discussionmentioning
confidence: 99%